Os agentes indígenas de saúde do Alto Xingu - Novo, Marina Pereira (2008)
In the context of restructuring the indigenous health policies over the last 20 years in Brazil, and the consequent creation of the Special Sanitary Indigenous Districts since 1999, the Indigenous Health Agents appear as central elements of this new model for indigenous health attention, since they are understood as possible links or translators between the traditional systems and the official biomedicine. Considering this context, my intention was, through the presentation of ethnographic data about the formation process and the performance of the Indigenous Health Agents at the Upper Xingu, to question the role attributed to them, as well as the model of differentiated attention where this role was proposed. Exactly because they occupy a border position between different medicaltherapeutic systems, the agents performances are involved in several ambiguities and conflicts, which result from the imprecise definition of their functions, as well as from the effective existing conditions for their acting in the spaces attributed to them. I intend to show that the Indigenous Health Agents have their role redefined twice: by the non-indigenous professionals who think of them as transmitters of the biomedical knowledge to the attended populations as well as by the indigenous themselves, who see them as sources of goods and services from national society, in the general context of the political appropriation of this role and its acting spaces by the upper-xinguanos and local leaders themselves.